2014
DOI: 10.1097/aln.0b013e3182a4441f
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Thrombocytopenia and Postoperative Outcomes after Noncardiac Surgery

Abstract: Background: Most studies examining the prognostic value of preoperative coagulation testing are too small to examine the predictive value of routine preoperative coagulation testing in patients having noncardiac surgery. Methods: Using data from the American College of Surgeons National Surgical Quality Improvement database, the authors performed a retrospective observational study on 316,644 patients having noncardiac surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 31 publications
6
58
3
5
Order By: Relevance
“…Thrombocytopenia is relatively common in the preoperative period, occurring in 6% of patients in the present investigation. Similar to recently published data from Glance and colleagues, 17 preoperative thrombocytopenia was associated with adverse patient outcomes including increased perioperative RBC requirements, higher rates of reoperation for bleeding, and greater hospital mortality. While the precise mechanism associating thrombocytopenia with poor patient outcomes remains unclear and causality cannot be established based on these data alone, there are several plausible explanations for poor outcomes in the setting of preoperative thrombocytopenia including a potential increase in perioperative blood loss in those with low starting PLT counts, a higher rate of transfusionassociated complications, and more severe systemic disease (diagnosed or occult) in patients with thrombocytopenia with PLT count serving as a surrogate marker for disease or as an inherent disease manifestation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thrombocytopenia is relatively common in the preoperative period, occurring in 6% of patients in the present investigation. Similar to recently published data from Glance and colleagues, 17 preoperative thrombocytopenia was associated with adverse patient outcomes including increased perioperative RBC requirements, higher rates of reoperation for bleeding, and greater hospital mortality. While the precise mechanism associating thrombocytopenia with poor patient outcomes remains unclear and causality cannot be established based on these data alone, there are several plausible explanations for poor outcomes in the setting of preoperative thrombocytopenia including a potential increase in perioperative blood loss in those with low starting PLT counts, a higher rate of transfusionassociated complications, and more severe systemic disease (diagnosed or occult) in patients with thrombocytopenia with PLT count serving as a surrogate marker for disease or as an inherent disease manifestation.…”
Section: Discussionsupporting
confidence: 79%
“…16 However, recent evidence suggests that preoperative thrombocytopenia is associated with significantly higher risk of blood transfusion and death in noncardiac surgery, prompting the authors to question recommendations against routine preoperative screening. 17 In clinical practice, administration of PLTs in those with thrombocytopenia is frequently performed in the preoperative period in an attempt to mitigate perioperative bleeding complications including RBC requirements, surgical blood loss, and reoperation for bleeding. However, evidence to support or guide such perioperative transfusion practices is lacking.…”
mentioning
confidence: 99%
“…Williamson et al, 17 as well as other investigators, found that, in medical and non-cardiac surgery patients, thrombocytopenia as a time-dependent covariate was independently associated with mortality. Similarly, Glance et al 47 recently reported that both preoperative thrombocytopenia and thrombocytosis were associated with reduced survival after surgery. According to our findings, postoperative thrombocytopenia was associated with short-term mortality, but the risk decreased linearly over the first 14 months (1.18 years) following surgery, but not after.…”
Section: Discussionmentioning
confidence: 78%
“…Both age and BMI have been associated with complications among gynecologic oncology patients(11, 14). Low albumin, low hematocrit, elevated creatinine, and thrombocytopenia are associated with poor performance status and have been associated with complications among a diversity of surgical patients(15-21). In regard to cancer biology, both white blood cells and platelets have been linked to aggressive cancer biology, poor prognosis, and postoperative complications among ovarian cancer patients(22-25).…”
Section: Methodsmentioning
confidence: 99%